Correlação da cintilografia de mama com a classificação imunoistoquímica dos tumores mamários - Henriques, Luciana Gurgel da Trindade Meira [UNESP] (2016)
Introduction: Breast carcinoma is one of the leading causes of deaths in the world and its early diagnosis and treatment have an important impact in the clinic evolution. The Immunohistochemical (IHC) profile determines the prognosis of the carcinoma and which is the best therapy to be established. Authors suggest that scintimammography could help immunohistochemistry (IHC) in these prognosis definitions. Methods: This study included patients with invasive breast carcinoma who were diagnosed in the period of 2011- 2013 at the Hospital das Clinicas of the Medical School of Botucatu. In all of the cases, IHC exams were performed, determining the proliferative index (PI) and the classification. The association between both results and the scintimammography (SMG) findings were analyzed. Results: of the 310 patients with invasive breast carcinoma diagnosed in the period, 243 had their classification and PI defined by the IHC. Normal SMG is associated to low PI and to hormonal therapy responsive classifications. The patients with altered SMG have had more chances of having a PI greater or equal to 14%, with high accuracy, high positive predictive valor and high sensibility, and are significantly associated to hormonal therapy irresponsive forms. More intense alterations are associated with forms of poor prognosis. Conclusion: altered SMG in patients with histological diagnosis of invasive breast carcinoma indicate a worse prognosis, as well as normaly indicates the existence of tumor classification with better response to hormonal chemotherapy. These findings do not allow the replacement of the immunohistochemistry prognosis profile for the scintimammography in the treatment of this disease, but can guide the prognosis and responsiveness to drug. Key Words: invasive breast carcinoma; immunohistochemistry; scintimammography; radioisotope; nuclear medicine.